Microstructure of the rapidly solidified alloy Bi34Sn63Ag3 - Gusakova, Olga V.; Shepelevich, Vasiliy G.; Gusakova, Sofia V. (Journal of the Belarusian State University. Physics, 2017)
The results of investigation into the microstructure, phase composition, grain structure, and texture as well as microhardness of Bi34Sn63Ag3 foils obtained by ultrafast quenching from the melt at the melt cooling rate 5 · 105 K/s are presented. It is shown that ultrafast quenching from the melt leads to the formation of the nanosized phase precipitations of bismuth and tin. The results obtained during analysis of the inclusion chords average sizes and of the specific surface for the interphase boundaries are considered. As demonstrated by studies of the grain structure, ultrafast quenching from the melt causes the formation of a microcrystalline structure of the foils. It has been found that in the foils the formed pronounced texture is gradually weakening from the side adjacent to the mold to the free solidified side. The nucleation texture formation is discussed. The changes in the foil microstructure and microhardness during aging at room temperature are illustrated. The observed decrease in microhardness is attributed to the decomposition of supersaturated solid solutions and to enlargement of the alloy particles during aging.